The Impact of Chemotherapy, Radiation and Epigenetic Modifiers in Cancer Cell Expression of Immune Inhibitory and Stimulatory Molecules and Anti-Tumor Efficacy - Jessica Ann Chacon; Keith Schutsky; Daniel J. Powell (Vaccines, 2016)
Genomic destabilizers, such as radiation and chemotherapy, and epigenetic modifiers are used for the treatment of cancer due to their apoptotic effects on the aberrant cells. However, these therapies may also induce widespread changes within the immune system and cancer cells, which may enable tumors to avoid immune surveillance and escape from host anti-tumor immunity. Genomic destabilizers can induce immunogenic death of tumor cells, but also induce upregulation of immune inhibitory ligands on drug-resistant cells, resulting in tumor progression. While administration of immunomodulatory antibodies that block the interactions between inhibitory receptors on immune cells and their ligands on tumor cells can mediate cancer regression in a subset of treated patients, it is crucial to understand how genomic destabilizers alter the immune system and malignant cells, including which inhibitory molecules, receptors and/or ligands are upregulated in response to genotoxic stress. Knowledge gained in this area will aid in the rational design of trials that combine genomic destabilizers, epigenetic modifiers and immunotherapeutic agents that may be synergized to improve clinical responses and prevent tumor escape from the immune system. Our review article describes the impact genomic destabilizers, such as radiation and chemotherapy, and epigenetic modifiers have on anti-tumor immunity and the tumor microenvironment. Although genomic destabilizers cause DNA damage on cancer cells, these therapies can also have diverse effects on the immune system, promote immunogenic cell death or survival and alter the cancer cell expression of immune inhibitor molecules.